The Influence of Innovation Management on the Effectiveness of Digital Learning Media Development - Muklis, Muklis (International Journal of Educational Insights and Innovations, 2025)
The development of digital technology has encouraged educational institutions to innovate in developing more interactive and adaptive learning media. This study aims to analyze the effect of innovation management on the effectiveness of digital learning media development. The research method used is a quantitative approach with a survey technique. Data were collected by distributing questionnaires to 75 respondents consisting of educators and learning media developers in higher education. Data analysis was performed using multiple linear regression to determine the relationship between innovation management variables (innovation planning, implementation, and evaluation) and the effectiveness of digital learning media development. The results show that innovation management has a significant effect on the effectiveness of digital learning media development, with the greatest contribution coming from the aspect of innovation implementation. These findings confirm that the success of learning media development is not only determined by technological capabilities, but also by the institution's ability to manage the innovation process systematically and sustainably. The implications of this study highlight the importance of implementing innovation management as a key strategy in improving the quality and effectiveness of digital learning media in the era of educational transformation.